Effect of social identity on the generation of electronic word-of-mouth (eWOM) on Facebook - Franklin Javier González-Soriano; Percy Samuel Marquina Feldman; Javier Alejandro Rodríguez-Camacho; Len Tiu Wright (Cogent Business & Management, 2020)
This study examines how social identity affects the generation of electronic word-of-mouth (eWOM). We develop a structural equation model (SEM) comprising self-enhancement, social capital, and social presence as explanatory variables of social identity. We propose that, through these variables, the social identity construct has a positive relation with eWOM and its generation on social media. We analyze this effect by empirically estimating the model using data obtained from Ecuadorian university students and test the relation between social identity and the generation of purchase experience comments on social media. We analyze the effect of each variable on the generation of purchase experience comments on Facebook. Our results confirm the influence of social identity on the generation of eWOM, showing that social capital is an important variable in this process.
Keywords: C12; C38; D91; M31; M37; 650; electronic word-of-mouth; social identity; social presence; self-enhancement; social capital